Subsurface Moisture Regulates Himalayan Groundwater Storage and Discharge. Issue 2 (18th May 2021) - Illien, L.; Andermann, C.; Sens‐Schönfelder, C.; Cook, K. L.; Baidya, K. P.; Adhikari, L. B.; Hovius, N.
Abstract: Through the release of groundwater, most mountain rivers run year‐round despite their small catchments and sporadic precipitation. This makes mountain ranges important sources of reliable freshwater for downstream populations in many parts of the world. However, due to a lack of ground instrumentation, little is known about groundwater dynamics in mountainous landscapes. Recent research has shown that the amount of moisture trapped in the soil and weathered rocks in the vadose zone can significantly buffer groundwater recharge and runoff but the wider recognition of this effect on major mountain systems has not been yet established. In this study, we test whether the moisture reservoir has an impact on hydrological fluxes in a steep Himalayan catchment during three monsoon seasons. We measured an array of parameters including relative seismic velocity changes from ambient noise correlations. This noninvasive technique allows us to monitor groundwater dynamics in conjunction with classical hydrological measurements. We found that the moisture saturation in the vadose zone controls the onset of groundwater recharge and runoff and therefore determines the annual water availability supplied by monsoon precipitation. We model this dynamic using a surface layer that has a finite storage capacity that controls the connectivity of surface flux to groundwater. The extension of this concept, which is thought to apply widely in flat and undulating landscapes, to steep mountain topography with thin and discontinuous soils underlain by regolith and bedrock has important implications for mountain hydrology. Plain Language Summary: The Nepal Himalayas supply essential water resources to a large part of the population of South Asia. Most of this water drains through a mountain groundwater reservoir that is poorly constrained. In steep landscapes, this reservoir is continuously losing water due to gravitational pull. Understanding how the reservoir fills and drains is crucial to the assessment of its sustainability and projection into the future with respect to global climate change. However, the relevant subsurface processes are generally challenging to observe due to limited access to the subsurface, particularly in steep mountain landscapes. We have used seismic ambient noise, ground vibrations continuously recorded by seismometers, to monitor the groundwater dynamics on a spatially integrated scale in a Himalayan valley. We show that the moisture content of a shallow layer controls the transfer of precipitation into the deeper groundwater reservoir during the Indian monsoon seasons. Our study highlights the need to anticipate the effects of changes of land use, soil cover conditions and rainfall regime, due to climate change, to better predict the future of freshwater resources in mountain landscapes. Key Points: Passive seismic interferometry reveals detailed insights into subsurface water storage variability in the Nepal Himalayas Vadose zone moisture saturation controls river discharge generation in a steep mountain landscape Freshwater delivery from high mountains is strongly dependent on subsurface conditions, which are rarely considered in these environments